O narrador e a paisagem: Milton Hatoum, Bernardo Carvalho e o fim do projeto de uma literatura nacional - Pedro Dolabela Chagas; Dárley Suany Leite dos Santos (Estudos de Literatura Brasileira Contemporânea)
In this paper, we discuss the end of the project of a national literature a s a guiding project of the Brazilian novel, having in mind the changes in the construction of the narrator and the representation of natural and social landscapes. To characterize such conditions, we review Echevarría’s proposition that the 19th - century La tin American novel adopted the local landscape as an identity symbol under the interpretive and authoritative mediation of non -fictional discourse. Then, we analyze Süssekind’s characterizations of fictional narrators that consolidated that function in Bra zil until the 20th century. In contrast, in Hatoum’s and Carvalho’s works, the multiplication of voices, the fragmentation of truths and the self - observation of the narrator block the mobilization of the landscape for an identity - function, in a deviation o f the founding assumptions of a national literature which indicates its demise as a common project – an important historical transition for the Brazilian novel.